Acute lymphoblastic leukaemia with osteolytic bone lesions: diagnostic dilemma. (11th August 2018) - Angsubhakorn, Natthapon; Suvannasankha, Attaya
Abstract : A previously healthy 37-year-old man presented with a 10-month history of intractable back pain. On examination, there was tenderness to palpation along lower thoracic and lumbar spine. Complete blood count showed mild anaemia but was otherwise unremarkable. Imaging studies revealed compression deformities with multiple osteolytic lesions involving multiple levels of the thoracic and lumbar spine. Bone marrow aspiration and biopsy were performed and demonstrated blast cells involving 80% of the bone marrow cellularity. Findings on flow cytometry were consistent with B-lymphoblastic leukaemia. He was subsequently started on hyper-CVAD (fractionated cyclophosphamide, vincristine, Adriamycin and dexamethasone) induction chemotherapy.